RELATIONAL DISSONANCE BETWEEN EMPLOYER AND EMPLOYEE EXPECTATIONS IN THE POST-WAR PERIOD (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Changes in employees' expectations regarding their future workplace and employers lead to relational dissonance. This necessitates modifications in decision-making related to employee motivation and the formation of organizational commitment.The purpose of the article. The purpose of this article is to identify relational dissonance between employer and employee expectations in the post-war period and to analyze changes in HR management functions in this context.Methods. The methodological basis of the study includes theoretical principles of management science and scholarly works by renowned economists in the field of human resource management. To address the research objectives, the study employs the dialectical method of scientific inquiry to examine the genesis of personnel management systems, as well as conceptual-logical analysis and a systematic approach to highlight challenges in HR management following the onset of war.Results. It has been established that the approach to management has evolved from "personnel management" through "human resource management" to a stage where people are not just resources but capital that creates added value. Each employee is an individual—unique, multifaceted, and diverse. The study confirms that new threats to Ukraine's labor potential are emerging. The primary threat is the rising number of individuals with disabilities. The second is early retirement, which implies a reduction in Ukraine's labor potential in the medium term. An additional challenge complicating HR management is the generational differences in the labor market. Employers and experts identify these differences across several dimensions: education and skills, attitude toward work and workplace relationships, physical capabilities, cognitive abilities and learning efficiency, family values, labor productivity, and communication skills. The study substantiates that the primary HR challenges for employers after the onset of war are, in order of priority: employee safety, team productivity, ensuring work continuity, and providing support and assistance to employees. Factors such as employee engagement, communication effectiveness, and skills development rank lower. Employees’ top expectations include attractive compensation packages, effective leadership, a friendly work environment, investment in training and development, clear career progression paths, and an organizational culture that fosters communication and knowledge-sharing. The new generation expects workplaces to accommodate family and affiliated values, as well as fair and objective motivation systems.Conclusion. Different generations have distinct attitudes toward work, values, expectations, and preferences related to employment and career development. Effective solutions in this context include tools that enhance employees’ knowledge, skills, and experience across age groups and facilitate the efficient transfer of organizational knowledge.
Keywords: threats to the labor potential of Ukraine, differences between generations in the work environment, education and skills, attitude to work, relationships at work, physical capabilities, mental abilities, efficiency of knowledge acquisition, family values, labor productivity, communication skills.